I, Amber Brown - Danziger, Paula, 1944-2004 (Danziger, Paula, 1944-2004. A is for Amber., 1999)
Because her divorced parents share joint custody of her, nine-year-old Amber suffers from lack of self-esteem and feels that she is a piece of jointly-owned property.